Fabrication and characterization of Fe2O3-OPEFB-PTFE nanocomposites for microwave shielding applications - Khamis, Ahmad Mamoun; Abbas, Zulkifly; Azis, Raba’ah Syahidah; Mensah, Ebenezer Ekow; Alhaji, Ibrahim Abubakar (John Wiley & Sons, 2022)
The development of microwave shielding nanocomposites based on recycled hematite nanoparticles, oil palm empty fruit bunch (OPEFB), and polytetrafluoroethylene (PTFE) was the main focus of this study. The complex permeability (μ′–jμ″), complex permittivity (ε′–jε″), reflection coefficient (S11), and transmission coefficient (S21) were determined using rectangular waveguide (RWG) connected to a vector network analyzer (VNA) in the frequency range of 8.2–12.4 GHz. The power loss, reflection loss, and total shielding effectiveness (SE) were calculated using the scattering parameters obtained through RWG. The results showed that the nanocomposites' microwave shielding properties can be controlled by tuning the percentage of Fe2O3 nanofiller in the nanocomposites. The values of ε′, ε″, μ′, and μ″ were enhanced by increasing the content of the recycled Fe2O3 nanofiller in the nanocomposites. At 10 GHz, the power loss values obtained for the nanocomposites ranged between 8.52 and 15.64 dB, while at 12.4 GHz, a maximum value of 16.32 dB was achieved by 25 wt%. nanocomposite. The total SE also increased with increasing Fe2O3 loading and a maximum value of 21.2 dB was achieved by 25 wt% nanocomposite at 12.4 GHz. The Fe2O3-OPEFB-PTFE nanocomposites have the potential to be used in microwave shielding applications in the frequency range 8.2–12.4 GHz.